2020
DOI: 10.2174/1573401316999200518095448
|View full text |Cite
|
Sign up to set email alerts
|

Several Components of the Lebanese Mediterranean Diet and Particular Sociodemographic, Medical and Lifestyle Factors may be Associated with Gastroesophageal Reflux Disease in Adults: A Cross-sectional Study in a Middle Eastern Setting

Abstract: Background: The prevalence of gastroesophageal reflux disease (GERD) is increasing worldwide and the related chronic symptoms can be associated with morbidity and poor quality of life. Objective: The objective of this study was to identify foods and beverages consumed by the Lebanese population, dietary habits, socio-demographic and lifestyle factors, health parameters and perceived stress, implicated in increasing GERD symptoms. Methods: This observational cross-sectional study was carried among Lebanese a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Keshteli et al [23] in a cross-sectional study reported that subjects with highest intake of fruits had 25% lower chance for developing GERD compared to those in the rst tertile intake; however, the intake of vegetables was not associated with GERD in crude and multivariable-adjusted models [34]. Another cross-sectional study conducted by Mary-Joe et al reported that some of the components of the Lebanese MedDiet might have protective effects on GERD [42]. Another study showed that meat consumption was directly correlated with GERD in Han Chinese [43].…”
Section: Discussionmentioning
confidence: 99%
“…Keshteli et al [23] in a cross-sectional study reported that subjects with highest intake of fruits had 25% lower chance for developing GERD compared to those in the rst tertile intake; however, the intake of vegetables was not associated with GERD in crude and multivariable-adjusted models [34]. Another cross-sectional study conducted by Mary-Joe et al reported that some of the components of the Lebanese MedDiet might have protective effects on GERD [42]. Another study showed that meat consumption was directly correlated with GERD in Han Chinese [43].…”
Section: Discussionmentioning
confidence: 99%